Respiratory motion-management in stereotactic body radiation therapy for lung cancer – A dosimetric comparison in an anthropomorphic lung phantom (LuCa). Issue 2 (November 2016) - Ehrbar, Stefanie; Perrin, Rosalind; Peroni, Marta; Bernatowicz, Kinga; Parkel, Thomas; Pytko, Izabela; Klöck, Stephan; Guckenberger, Matthias; Tanadini-Lang, Stephanie; Weber, Damien Charles; Lomax, Antony
Abstract: Background and purpose: The objective of this study was to compare the latest respiratory motion-management strategies, namely the internal-target-volume (ITV) concept, the mid-ventilation (MidV) principle, respiratory gating and dynamic couch tracking. Materials and methods: An anthropomorphic, deformable and dynamic lung phantom was used for the dosimetric validation of these techniques. Stereotactic treatments were adapted to match the techniques and five distinct respiration patterns, and delivered to the phantom while radiographic film measurements were taken inside the tumor. To report on tumor coverage, these dose distributions were used to calculate mean doses ( Dmean ), changes in homogeneity indices (Δ H 2 - 98 ), gamma agreement, and areas covered by the planned minimum dose ( A>Dmin ). Results: All techniques achieved good tumor coverage ( A>Dmin  > 99.0%) and minor changes in Dmean (±3.2%). Gating and tracking strategies showed superior results in gamma agreement and Δ H 2 - 98 compared to ITV and MidV concepts, which seem to be more influenced by the interplay and the gradient effect. For lung, heart and spinal cord, significant dose differences between the four techniques were found ( p  < 0.05), with lowest doses for gating and tracking strategies. Conclusion: Active motion-management techniques, such as gating or tracking, showed superior tumor dose coverage and better organ dose sparing than the passive techniques based on tumor margins.